G238(P) Accuracy and confidence in the recognition of common otopathology by NCHDs in the Paediatric Emergency Department. (27th April 2016) - McGlacken-Byrne, SM; Johnston, NF; Fitzsimons, JJ
Abstract : Introduction: The ENT examination is a routine component of the paediatric Emergency Department (ED) assessment. In spite of this, there is a paucity of formal education on recognising common ear pathologies. Over-diagnosis of otopathology can result in missed infection foci and inappropriate antibiotic use; under-diagnosis can lead to the sequelae of untreated suppurative otopathology. We assessed the confidence and ability of our paediatric ED doctors at recognising otopathology. Methods: Paediatric non-consultant hospital doctors across all training grades completed a questionnaire: 15 slides, 9 with normal tympanic membranes and 6 with otopathology. Trainees chose the diagnosis from 7 options, unaware of the proportion of pathology versus normal ears. Confidence in otoscopic diagnosis was assessed using a 3-point Likert scale. Statistical analyses were performed using SPSS/Excel. Results: 35 trainees completed the questionnaire. Trainees identified abnormal tympanic membranes 53.3% of the time (range 33–87%), making correct specific diagnoses 40% of the time (range 13–73%). While our images of AOM were correctly identified 67% of the time (range 0–100%), trainees citing AOM as the diagnosis were correct only 50% of the time (range 0–100%). Mean confidence level for all responses was 2.14. Incorrect and correct diagnoses were made with mean confidence levels of 1.98 and 2.26 respectively. 61.5% of incorrect diagnoses were made either "fairly confidently" or "very confidently". There was no correlation between trainees' mean confidence levels and total aggregrate scores (Spearman's r = -0.265, p = 0.124). No training grade reported higher mean confidence levels in their responses than another on ANOVA analysis (p = 0.207). No training grade performed significantly higher than another on ANOVA analysis (p = 0.751). Conclusion: Trainees had difficulty identifying images of normal ears and otopathology. This can be extrapolated to ED otoscopy assessment. There is a lack of confidence amongst trainees in their ability to recognise otopathology, even among higher scoring trainees. Of concern is the substantial number of incorrect diagnoses made "very confidently", possibly resulting in missed foci of infection. We plan to incorporate formal basic ENT training into our teaching sessions.